(untitled) (Bangladesh Journal of Medicine, 2022)
CA-125 is a serum marker that is raised in various malignant and non- malignant conditions, but a very high rise (>1000 U/mL) almost always suggests ovarian malignancy. Here we report a rare case of tuberculous peritonitis in a 58-year-old woman who presented with gradually progressive abdominal distension and weight loss, and her CA-125 level was >1000 U/mL. Initially suspecting this as a case of ovarian malignancy, ascitic fluid study to detect malignant cells and a contrast CT scan of the abdomen was done, but the results didn’t suggest any malignancy. Finally, diagnostic laparoscopy was done and tuberculous peritonitis was diagnosed by peritoneal biopsy and histopathology. This case is an excellent example showcasing the importance of tissue diagnosis over indirect supportive tests, and it also suggests that clinical suspicion of tuberculosis in an endemic zone should always be there even if the patient has very high CA-125 level. Bangladesh J Medicine 2022; 33: 49-51